1993
DOI: 10.1029/92wr01820
|View full text |Cite
|
Sign up to set email alerts
|

The dipole flow test: A new single‐borehole test for aquifer characterization

Abstract: A new single‐borehole measurement technique for confined aquifers, the dipole flow test, yields the vertical distributions of the horizontal hydraulic conductivity, the vertical hydraulic conductivity, and the specific storativity when applied to different borehole intervals. The test utilizes straddle packers to isolate two chambers in the borehole, pressure transducers to monitor drawdown in them, and a small pump to create a dipole flow pattern in the aquifer by pumping water at a constant rate from the aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
2
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(112 citation statements)
references
References 35 publications
1
108
2
1
Order By: Relevance
“…For example, in order to interpret WBF logging measurements, a transmissivity or hydraulic conductivity estimate obtained through aquifer testing is often required. Likewise, in order to interpret dipole-flow test measurements, a test that estimates the vertical variations in hydraulic conductivity in a single borehole using a three-packer tool [Kabala, 1993;Butler et al, 1998], an estimate of the anisotropy ratio between vertical and radial hydraulic conductivity, is required. Other methods have a more direct interpretation but may provide less reliable estimates.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in order to interpret WBF logging measurements, a transmissivity or hydraulic conductivity estimate obtained through aquifer testing is often required. Likewise, in order to interpret dipole-flow test measurements, a test that estimates the vertical variations in hydraulic conductivity in a single borehole using a three-packer tool [Kabala, 1993;Butler et al, 1998], an estimate of the anisotropy ratio between vertical and radial hydraulic conductivity, is required. Other methods have a more direct interpretation but may provide less reliable estimates.…”
Section: Introductionmentioning
confidence: 99%
“…The water flows from the upper production chamber to the injection chamber through the pump and from injection chamber to the production chamber through the porous formation. Dipole flow has been studied in several recent publications [Kabala, 1993; MacDonald and Kitanidis, 1993; Zlotnik andLedder, 1994, 1996]. In these investigations the aquifer is regarded as a deterministic anisotropic formation …”
Section: Dipole Wellmentioning
confidence: 99%
“…A radial clean-up zone is created around the well. Previous work on recirculation wells [Philip and Walter, 1992;Kabala, 1993;Herrling et al, 1991;Gvirtzman and Gorelick, 1992] has shown that a single well can achieve a zone of cleanup that extends radially 2 to 3 times the aquifer thickness. Groundwater entering this zone under regional flow conditions will be recycled and cleaned.…”
Section: In-well Vapor Strippingmentioning
confidence: 99%